The teacher-student interaction in the university stage: the influence in the classroom atmosphere - Antonio PALOMINO MARTÍN; Eduardo RAMOS VERDE (Aula, 2020)
In this study, we analyze the interaction that occurs in some university classrooms between teacher and student in the various branches of knowledge. They involved 15 teachers and 560 students. The analyzes allow us to say that there are very significant differences between categories of Distance and Closeness, showing the first of a total of 359 evidence against the 532 of the second, indicating a clear inclination towards positive interaction between teachers and students.